Legitimacy and Organizational Sustainability - Thomas, Tom E. (Journal of business ethics, 2012)
The literature regarding social and environmental sustainability of business focuses primarily on rationales for adopting sustainability strategies and operational practices in support of that goal. In contrast, we examine sustainability from a perspective that has received far less research attention—attitudes that inform managerial decision-making. We develop a conceptual model that identifies six elemental categories of attitudes that can be held independently or aggregated to yield a meta-attitude representing the legitimacy of sustainability. Our model distinguishes among three types of internally held attitudes and externally perceived subjective norms: pragmatic, moral, and cognitive. We propose a refinement of Ajzen’s (In: Kuhl J, Beckmann J (eds) Action control: from cognition to behavior, 1985; Organ Behav Hum Decis Process 50:179–211, 1991) Theory of planned behavior (TPB) that incorporates these sub-categories of personal attitudes and subjective norms. Practical implications are discussed including how organizations considering adopting sustainability programs might use the model as a conceptual tool to help achieve and assess program success.